Dusk but not dawn burrow emergence rhythms of Nephrops norvegicus (Crustacea: Decapoda) - Sbragaglia, Valerio (2013)
The Norway lobster, Nephrops norvegicus, can be captured by haul nets only during the emergence from its burrow. In the last few decades, an extensive field research revealed distinct diel (24-h-based) catchability patterns at different depths. Laboratory experiments suggested that burrow emergence (used as a proxy of catchability) is endogenously controlled via a circadian system. Results were usually presented in terms of mean effects without a quantification of inter-individual variability and arrhythmia. Here, we studied the burrow emergence of 52 adult Nephrops by an infrared actograph endowed with an artificial burrow. Animals were exposed to 12-12 h light-darkness cycle, simulating photic condition of the lower shelf. Forty-five animals showed rhythmic emergence (87%), while seven were arrhythmic (13%). Rhythmic animals were clustered according to their timing of emergence: 54% at dusk and 4% at dawn. Moreover, other animals showed fully diurnal or nocturnal emergence (10% and 19%, respectively). The comparison of our results with those derived from temporally scheduled trawling indicates that bimodal catch patterns observed in shelf populations are poorly observed during individual experiments in the laboratory, where the same light conditions are simulated. Nephrops burrow emergence seems to be the result of a mixed endogenous-exogenous control, while arrhythmia could also be present in the wild.